DASHBOARD SISTEM INFORMASI EKSEKUTIF PENJUALAN - Susan Dian Purnamasari; Alek Wijaya (Jurnal Ilmiah Matrik, 2017)
Currently PT Semen Baturaja (Persero) Tbk already has a sales information system that has been integrated with enterprise resource planning (ERP) company system. However the existing information system provides more information relating to the course of sales operations, sales report submission is still less organized and still using office applations. The report is also not appropriate for the executive. The high level of directors mobility makes the required sales data must be fast and accurately received by the board of directors. Therefore, PT Semen Baturajaic (Persero) Tbk is in need of an information system that serves as a means to view all sales data in the long run and can be viewed anytime without having to wait for reports from sales staff. This research generates executive sales information systems at PT Semen Baturaja (Persero) Tbk by utilizing business intelligence that is able to provide detailed information on sales in chart or graphic display